Does banks’ dual holding affect bank lending and firms’ investment decisions? Evidence from China - Pan, Xiaofei; Tian, Gary Gang (Journal of Banking & Finance, 2015)
This study investigates the effect of banks’ dual holding on bank lending and firms’ investment decisions using a sample of listed firms in China. We find that dual holding leads to easier access to bank loans, a result that is more pronounced for non-state-owned enterprises (non-SOEs) than SOEs. We also find that dual holding distorts banks’ lending decisions and harms the investment efficiency for SOEs, while resulting in optimal lending decisions and enhanced investment efficiency for non-SOEs. For non-SOEs, further analysis suggests that optimal lending decisions and efficient investment can be achieved for firms with higher ownership concentration, and firms in which the family and foreign investors are the controlling shareholders. We argue that, in emerging markets, whether a bank plays a monitoring role by directly holding the debt and equity claims of companies relies heavily on whether the potential collusion between firm executives and bank managers can be averted, which in turn is determined by the firms’ governance framework and ownership structure.